PEMBERDAYAAN SEKTOR INFORMAL DALAM UPAYA PENINGKATAN PENDAPATAN MASYARAKAT - Amir Dedoe (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2013)
This research aims to explain wheater government intervention in the form of capitalization, education, training/skill, and organization estabilishment could formators of informal sector in increasing their income, and analyze the impact of government intervention on the increase of community income of informal sector. This research was a case study used a descriptive-qualitative analysis. The data were obtained through observation and in depth interview. The sample was selected using purposive sampling method. Since the actors of informal sector working as sidewalk traders were divided into certain groups, the key informant were also selected purposively. These groups were the sidewalk traders who were not married and that been working for less than five years and the ones who were maried and had been working for more than five years. The data were than processed using qualitative analysis. The results show that the participation of informant in informal sector activity as sidewalk traders in Sungailiat village is caused by their family’s economic condition. The factors affecting the business of sidewalk trades are economic need and limited capital. The prospect of business development of sidewalk traders indicates a positive trend by obtaining capital aid from the local government of Bangka Regency accompanied by forming institution. By such and aid, the sidewalk traders could increase their business volume and develop it by making use of the strengthening of existing institution.